OP0185 Efficacy of Canakinumab in Biologic NaÏVe versus Previously Biologic-Exposed SJIA Patients. (10th June 2014) - Quartier, P.; Grom, A.; Ruperto, N.; Brunner, H.; Schikler, K.; Erguven, M.; Goffin, L.; Hofer, M.; Kallinich, T.; Marzan, K.; Gaillez, C.; Lheritier, K.; et al.
Abstract : Background: Canakinumab (CAN), a selective, fully-human anti-IL-1β monoclonal antibody is approved for SJIA in over 30 countries. Efficacy and safety of CAN over 12 weeks have been demonstrated in 2 phase III trials. 1 In these trials, >60% of the pts received a previous biologic and were switched to CAN due to lack of efficacy or for safety reasons, and may be more refractory to another biologic therapy. Objectives: To present a post-hoc evaluation of CAN efficacy in biologic-naïve (BN) pts and those previously exposed to biologics (BE) during the first 12-weeks. Methods: Pooled data from CAN naïve pts, enrolled in two phase III trials 1 and an extension phase (up to interim data lock 10 August 2012) were considered. Pts (2–19 yrs) with active SJIA were enrolled and received CAN 4 mg/kg or placebo sc every 4 weeks for 12 weeks. CAN naïve pts who entered the trials and received at least one dose of CAN were included in this analysis (N=178 CAN naïve pts). Descriptive efficacy analyses of adapted ACR-JIA responses at Week 12 are provided for the BN and BE pts groups. Results: At baseline, there were 66 (37%) BN pts whereas anakinra (ANA), tocilizumab (TCZ), etanercept (ETN) and adalimumab (ADA), were the biologics received by 78 (44%), 10 (6%), 58 (33%) and 9 (5%) pts, respectively. The main reasons for discontinuation of biologics in BE group (n=112) was lack of efficacy (ANA, n=32; TCZ, n=7; ETN, n=56; ADA, n=9) or safety/tolerability (ANA, n=20; TCZ, n=4, ETN, n=0). At Week 12, the BN and BE groups were similar in aACR-JIA 30 and 50 response rates. Numerically higher aACR-JIA 70 and 90 response rates were achieved in BN vs. BE pts (Table). aACR-JIA 70 and 90 response rates were similar in pts previously exposed to ANA vs those not exposed to ANA at 12 weeks (aACR-JIA70: 58% vs.63% and aACR-JIA 90:47% vs 50%). Compared to pts who discontinued ANA due to lack of efficacy, there was a trend towards higher aACR-JIA 70 and 90 response rates at Week 12 in pts who stopped ANA for other reasons (aACR-JIA70: 34% vs.74%; aACR-JIA90: 25% vs. 63%). A higher aACR-JIA 30, 50, 70 and 90 response rates were observed in TCZ naïve pts vs. those pts exposed to TCZ (n=10) [aACR-JIA30: 71% vs.50%; aACR-JIA50: 70% vs. 50%; aACR-JIA70: 61% vs.50%; aACR-JIA90: 49% vs. 40%]. Higher aACR-JIA 70 and 90 responses were observed for ETN naïve pts vs. those exposed to ETN [aACR-JIA70: 67% vs. 48%; aACR-JIA90: 58% vs. 31%]; while ADA- naïve pts had similar responses to CAN as ADA-exposed pt (aACR-JIA 70: 61% vs 56%) and they had higher aACR-JIA 90 response (aACR-JIA90: 50% vs. 22%). Conclusions: In general, BE pts achieved aACR-JIA 50, 70 and 90 responses to CAN quickly in the first 2 weeks, and maintained their response up to Week 12; albeit at a numerically lower level than BN pts. These data support the consistent efficacy of CAN across different subgroups of pts. References: Ruperto N, et al. N Engl J Med 2012;367(25). Disclosure of Interest: P. Quartier Grant/research support: Abbvie, BMS, Chugai-Roche, Novartis, Pfizer and SOBI, Consultant for: Abbvie, Chugai-Roche, Novartis, Pfizer, Servier and SOBI, Speakers bureau: Chugai-Roche, MEDIMMUNE, Novartis, Pfizer, A. Grom Consultant for: Novartis, Roche, NovImmune, N. Ruperto Grant/research support: To Gaslini Hospital: Abbott, Astrazeneca, BMS, Centocor Research & Development, Eli Lilly and Company, "Francesco Angelini", Glaxo Smith & Kline, Italfarmaco, Novartis, Pfizer Inc., Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth Pharmaceuticals Inc., Speakers bureau: Astrazeneca, Bristol Myers and Squibb, Janssen Biologics B.V., Roche, Wyeth/Pfizer, H. Brunner Consultant for: Novarits, Roche, Astrazeneca, Celgene, Pfizer, Janssen, UCB, GSK, BMS, Speakers bureau: Novartis, K. Schikler Grant/research support: Pfizer, Novartis, Abbvie, Roche, Genentech, Speakers bureau: Abbvie, Novartis, M. Erguven: None declared, L. Goffin Consultant for: Novartis, Pfizer, M. Hofer Grant/research support: Novartis, Pfizer, Abbvie, T. Kallinich Grant/research support: Novartis, Speakers bureau: Roche, Novartis, ALK, K. Marzan Grant/research support: Novartis, C. Gaillez Employee of: Novartis, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, K. Abrams Shareholder of: Novartis, Employee of: Novartis, A. Martini Grant/research support: The Gaslini Hospital, which is the public Hospital where I work as full time employee, has received contributions to support the PRINTO research activities from the following companies: Bristol Myers and Squibb, Centocor Research & Development, Glaxo Smith & Kline, Novartis, Pfizer Inc, Roche, Sanofi Aventis, Schwarz Biosciences GmbH., Speakers bureau: Abbott, Bristol MyersSquibb, Astellas, Behringer, Italfarmaco, MedImmune, Novartis, NovoNordisk, Pfizer, Sanofi, Roche, Servier, D. Lovell Grant/research support: National Institutes of Health- NIAMS, Consultant for: Astra-Zeneca, Centocor, Amgen, Bristol Meyers Squibb, Abbott, Pfizer, Regeneron, Roche, Novartis, UBC, Forest Research Institute, Horizon, Johnson & Johnson, Speakers bureau: Novartis, Roche DOI: 10.1136/annrheumdis-2014-eular.1099